2012
DOI: 10.1071/rdv24n1ab104
|View full text |Cite
|
Sign up to set email alerts
|

104 Birth of First Buffalo (Bubalus Bubals) Calf Following Embryo Splitting and Polymerase Chain Reaction Sexing at Blastocyst Stage

Abstract: Embryo-splitting technology provides an effective procedure for increasing the number of transferable embryos per donor, producing genetically identical offspring and facilitating embryo sexing. The ability to identify the sex of embryos before transfer will offer a reliable, economical and practical procedure for buffalo breeding. In this study, we have assessed the feasibility of production of offspring with controlled sex in buffalo by first comparing the effect of blastocyst quality on the viability of dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Conception rates did not differ between adult buffaloes and buffalo heifers; however there was a difference between bulls (Tasripoo et al, 2014). Most studies in buffaloes have reported the use of sexed semen fur insemination after an estrus synchronization protocol (Zhang et al, 2011). A recent study, however, evaluated the insemination of 4521 swamp or crossbred buffaloes during natural estrus with X-sorted semen from river buffaloes and recorded a 48.5% pregnancy rate and 87.6% sex accuracy (Yang and Pang, 2010).…”
Section: Sperm Sexingmentioning
confidence: 94%
See 4 more Smart Citations
“…Conception rates did not differ between adult buffaloes and buffalo heifers; however there was a difference between bulls (Tasripoo et al, 2014). Most studies in buffaloes have reported the use of sexed semen fur insemination after an estrus synchronization protocol (Zhang et al, 2011). A recent study, however, evaluated the insemination of 4521 swamp or crossbred buffaloes during natural estrus with X-sorted semen from river buffaloes and recorded a 48.5% pregnancy rate and 87.6% sex accuracy (Yang and Pang, 2010).…”
Section: Sperm Sexingmentioning
confidence: 94%
“…The in vivo procedures involve induction of multiple ovulation, breeding and non-surgical recovery of embryos which are then transferred to synchronized recipients Inherently poor reproduction and seasonality in buffalo warrants the use of advanced reproductive technologies in this species. Efforts at multiple ovulation and embryo transfer in buffaloes have resulted in the birth of calves in many countries by transfer of fresh (Zhang et al, 2011) or cryopreserved embryos, however, the efficiency in terms of super ovulatory response and recovery of transferrable embryos continue to be low. Attempts to improve the ovulatory responses in buffaloes have shown marginal improvements (Tasripoo et al, 2014).…”
Section: In Vivo Production Of Embryomentioning
confidence: 99%
See 3 more Smart Citations